Invasive Pasteurella multocida Infections – Report of Five Cases at a Minnesota Hospital, 2014. (19th February 2016) - Talley, P.; Snippes‐Vagnone, P.; Smith, K.
Summary: During October 2014, the Minnesota Department of Health was notified of five Hospital A patients with Pasteurella multocida bacteraemia; three had died. Human soft tissue infection with P. multocida typically results from cat or dog bites or scratches. Invasive infection, defined as a P. multocida isolate from a usually sterile site, is rare. We evaluated P. multocida isolations at Hospital A, compared with other Minnesota hospitals to understand invasive infection trends. A case was defined as clinically confirmed P. multocida in a Minnesota resident during 2012–2014. All hospital laboratories were queried; Fisher's exact test was used for comparison. Medical charts were reviewed for 2014 Hospital A patients with P. multocida infections. The Minnesota clinical laboratories survey response rate was 79% (63/80). At Hospital A, proportion of P. multocida isolates from usually sterile sites increased from 0% (0/2) during 2012 to 11% (1/9) during 2013, and to 86% (5/6) during 2014. The proportion of patients with P. multocida isolated from sterile sites was 35% (6/17) at Hospital A compared with 10% (58/583) statewide during 2012–2014 combined ( P  <   0.05). Among 2014 Hospital A patients with invasive P. multocida infection, all five were men; median age was 70 (range: 44–78) years. Four were temporally clustered within a 33‐day period; three of those had bacteraemia on admission, making hospital acquisition possible in only one. Among five bacteraemia patients, four had cirrhosis and/or skin ulcerations, and three died. The proportion of invasive P. multocida cases was substantially higher at Hospital A during 2014. No epidemiologic links between patients were found. Three had known pet exposure. Collaborative educational efforts of chronically ill pet owners by physicians and veterinarians can acknowledge the health benefits of pet ownership, while minimizing risk for serious invasive zoonotic infections, including those caused by P. multocida .